Controlled Crystallinity of TiO2 Layers Grown by Atmospheric Pressure Spatial Atomic Layer Deposition and their Impact on Perovskite Solar Cell Efficiency. (30th September 2022) - Zimmermann, Eugen; Wong, Ka Kan; Seewald, Tobias; Kalb, Julian; Steffens, Jonathan; Hahn, Giso; Schmidt-Mende, Lukas
Abstract : Atmospheric Pressure Spatial Atomic Layer Deposition (AP-SALD) is an upcoming deposition technique suitable for a variety of materials and combines the benefits of a regular atomic layer deposition with a significantly increased deposition rate at ambient conditions. In this work, amorphous and anatase TiO2 layers are fabricated by AP-SALD via systematic variation of process conditions such as temperature, reactant (H2 O and O3 ), and posttreatment. The formed layers are characterized for their structural and optoelectronic properties and utilized as a hole-blocking layer in hybrid perovskite solar cells. It is found that TiO2 layers fabricated at elevated deposition temperatures possess strong anatase character but expose an unfavorable interface to the perovskite layer, promoting recombination and lowering the shunt resistance and open circuit voltage of the solar cells. Therefore, the interface is essential for efficient charge extraction, which can be significantly improved by controlling the process parameters.